2019
DOI: 10.1186/s13027-019-0244-7
|View full text |Cite
|
Sign up to set email alerts
|

A correlation study of BK Polyoma Virus infection and prostate Cancer among Sudanese patients - immunofluorescence and molecular based case-control study

Abstract: Background Polyomavirus hominis1, also called BK virus (BKV) is a well-known etiological agent of renal transplant nephropathy and cystitis. Recently, it got great attention from the researcher as a principal predisposing factor for different kinds of cancers including prostate cancer (PCa). Thus, this study aims to determine the correlation between BKV infection and PCa through a descriptive case-control based study. Methods A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…A total of 8 samples from our previous work on BKV were studied in this investigation [25]. These samples were randomly selected from 21 positive samples.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 8 samples from our previous work on BKV were studied in this investigation [25]. These samples were randomly selected from 21 positive samples.…”
Section: Study Populationmentioning
confidence: 99%
“…In Sudan, the relationship between viruses and cancer has been studied in only a limited studies [23,24]. In our previous study, the existence of the relationship between BKV and prostate cancer was determined [25] and the molecular characterization of BKV was described because only a few researchers have addressed BKV Subtypes.However, most previous studies have focused only on the isolates related to BKV nephropathy. The effect of each subtype on the clinical implications had previously been highlighted by various researchers [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…To date, strongly consistent evidence indicates that the BK virus (BKV) is a predisposing factor for different kinds of cancers, including prostate cancer [30,31], while other viruses, such as EBV, CMV, HSV2, HHV-8, XMRV, and HIV have inconsistent or null associations with prostate cancer. Mischitelli et al [32] investigated the presence of BKV sequences in urine, blood, and fresh prostate cancer samples, utilizing a quantitative PCR assay.…”
Section: Infections In Prostate Cancer Etiologymentioning
confidence: 99%
“…More and more studies suggest that there is a close link between the virus and prostate cancer. Recent studies have suggested that early detection of the virus may help reduce the risk of prostate cancer caused by the virus (108,109). Previous studies have found that the prostate may be the site of HPV replication (110), and most studies have shown that HPV is closely related to prostate cancer (111,112).…”
Section: Virusmentioning
confidence: 99%